1998
DOI: 10.1111/j.1151-2916.1998.tb02507.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post‐Precipitation Treatment on the Pore‐Structure Stability of Sol‐Gel‐Derived Lanthanum Zirconate

Abstract: The importance of post-precipitation treatments (porefluid exchange and its removal) on the evolution of the texture of coprecipitated lanthanum zirconate has been investigated. The nature of the pore fluid and the type of fluid-removal (drying) process have shown a profound effect on the aggregate structure (packing of primary particles within the aggregates of the gel). Exchanging the pore fluid with organic fluids such as ethanol or tetrahydrofuran resulted in higher specific surface area, larger pore volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…2. In agreement with previous studies [8][9][10][11][12][13], the alcoholic gelled media give xerogels with higher specific surface area than the ones obtained from aqueous gelled media.…”
Section: Aqueous and Alcoholic Xerogels Microstructuresupporting
confidence: 92%
See 1 more Smart Citation
“…2. In agreement with previous studies [8][9][10][11][12][13], the alcoholic gelled media give xerogels with higher specific surface area than the ones obtained from aqueous gelled media.…”
Section: Aqueous and Alcoholic Xerogels Microstructuresupporting
confidence: 92%
“…Thus, the beneficial action of alcohol was demonstrated experimentally, and nowadays alcohol washing is commonly used to obtain ultrafine dispersed powders [9]. To explain the effect of ethanol washing on precipitates, a number of authors argued that, since it has a surface tension less than water, the maximum capillary tension inside the network of the evaporating gel is kept at a minimum level; accordingly, the resulting dried xerogels are crack-free and have larger specific surface area [5,10,11]. According to other authors [7,9], assuming that the formation of agglomerates is the result of bridging among individual particles due to surface hydroxyl groups [12,13], alcohol washing would prevent or limit such a bridging action by substitution of hydroxyls by ethoxy groups.…”
Section: Introductionmentioning
confidence: 97%
“…For example, the S BET values of the 8FD and 8OD samples are very similar (66.82 m 2 g À 1 versus 61.20 m 2 g À 1 ). Likewise, Nair et al [54] reported that coprecipitated lanthanum zirconate precipitates dehydrated by FD and OD present essentially identical surface areas. The higher agglomeration in powders dehydrated by FD than by other methods is visible in the SEM images (Fig.…”
Section: Powder Characteristics and Their Relations To The Dehydratiomentioning
confidence: 95%
“…The initial endothermic peak at ∼90°C in the DTA trace is due to the loss of volatile water; two exothermic peaks at ∼240°a nd 450°C are probably due to the decomposition of ethanol. 8 This corresponds to a continuous weight loss in the TGA trace up to a temperature of ∼800°C. The final weight loss is ∼24% of the initial sample weight.…”
Section: (1) Thermal Analysismentioning
confidence: 99%